Pharmacological Targeting of Microglial Activation: New Therapeutic Approach - Liu, Cai-Yun; Wang, Xu; Liu, Chang; Zhang, Hong-Liang (Frontiers in Cellular Neuroscience, 2019)
Mounting evidence suggests that neuroinflammation is not just a consequence but a vital contributor to the development and progression of Parkinson's disease (PD). Microglia in particular, may contribute to the induction and modulation of inflammation in PD. Upon stimulation, microglia convert into activated phenotypes, which exist along a dynamic continuum and bear different immune properties depending on the disease stage and severity. Activated microglia release various factors involved in neuroinflammation, such as cytokines, chemokines, growth factors, reactive oxygen species (ROS) and reactive nitrogen species (RNS), and prostaglandins (PGs). Further, activated microglia interact with other cell types (e.g. neurons, astrocytes and mast cells) and are closely associated with α-synuclein (α-syn) pathophysiology and iron homeostasis disturbance. Taken together, microglial activation and microglia-mediated inflammatory responses play essential roles in the pathogenesis of PD and elucidation of the complexity and imbalance of microglial activation may shed light on novel therapeutic approaches for PD.